Overestimated nitrogen loss from denitrification for natural terrestrial ecosystems in CMIP6 Earth System Models - Maoyuan Feng; Shushi Peng; Yilong Wang; Philippe Ciais; Daniel S. Goll; Jinfeng Chang; Yunting Fang; Benjamin Z. Houlton; Gang Liu; Yan Sun; Yi Xi (Nature Communications, 2023)
Abstract Denitrification and leaching nitrogen (N) losses are poorly constrained in Earth System Models (ESMs). Here, we produce a global map of natural soil 15N abundance and quantify soil denitrification N loss for global natural ecosystems using an isotope-benchmarking method. We show an overestimation of denitrification by almost two times in the 13 ESMs of the Sixth Phase Coupled Model Intercomparison Project (CMIP6, 73 ± 31 Tg N yr−1), compared with our estimate of 38 ± 11 Tg N yr−1, which is rooted in isotope mass balance. Moreover, we find a negative correlation between the sensitivity of plant production to rising carbon dioxide (CO2) concentration and denitrification in boreal regions, revealing that overestimated denitrification in ESMs would translate to an exaggeration of N limitation on the responses of plant growth to elevated CO2. Our study highlights the need of improving the representation of the denitrification in ESMs and better assessing the effects of terrestrial ecosystems on CO2 mitigation.